Regional integration in the West African economic and Monetary Union (WAEMU): Complementarity or competition? - Alastaire Sèna Alinsato (Economies, 2022)
This paper analyzes and characterizes the nature of the interactions between countries of the West African Economic and Monetary Union (WAEMU) over the period 1995–2015. The analysis uses sigma-convergence on the one hand and the Dendrinos-Sonis spatial competition model estimated by the SUR method on the other hand. The results show a lack of convergence of living standards and support the idea of income polarization in space; these results also support the idea of a very poorly integrated region with relatively competitive interrelationships. The paper suggests the acceleration of regional integration in the WAEMU region combined with the implementation of inclusive integration policies that promote each member's comparative advantage.
Keywords: 330; competition; complementarity; Dendrinos-Sonis model; sigma-convergence